A guide for implementing a patent strategy : how inventors, engineers, scientists, entrepreneurs, and independent innovators can protect their intellectual property - Rimai, Donald S (Wiley, 2019)
"This book is aimed at the innovators who drive the advances from which we all benefit.  This includes scientists, engineers, technicians, managers, and entrepreneurs who want to financially benefit from their innovations.  The book describes how to build patent portfolios that will properly protect your technology and be of financial benefit.  The tools that innovators need to have to generate patents are presented in detail"--
"Sales handles: - A sequel to the bestselling book on Patent Engineering published by Wiley-Scrivener in 2016. - The book teaches you how to build a patent portfolio, how to protect and preserve your intellectual property, and how to financial benefit from it. Market description: Primary audience: This book is primarily aimed at scientists, engineers, technicians, managers, and entrepreneurs working in all industries and sectors. Secondary audience: This book would be suitable for engineering, science, and business students seeking understand the value and function of patents"--
Background for developing and implementing a patent strategy -- The structure of a patent -- The path to obtaining patents -- Identifying patentable inventions -- Identifying what has yet to be invented -- Prioritizing the inventions -- Prioritizing your patent applications -- Proposing and writing claims -- Conducting prior art searches -- The mindsets of innovators and attorneys and other cautionary notes -- Reviewing your proposed patent applications -- Writing your patent applications -- The next step : prosecution of your patent application -- What next? -- Final thoughts.
Includes bibliographical references and index.
Keywords: Patent laws and legislation -- United States; Patents -- United States; LAW / Intellectual Property / General